"Green" composites using bioresins from agro‐wastes and modified sisal fibers. Issue 1 (5th October 2017) - Patil, Namrata V.; Rahman, Muhammad M.; Netravali, Anil N.
Abstract : "Green" composites were fabricated using modified sisal fibers and agro‐waste derived resins from nonedible protein and starch in a simple and cost‐effective manner. Sisal fibers were modified using a novel combination of mercerization followed by heat treatment under a pre‐determined tension which improved their Young's modulus by over 200% (from 5.5 to 16.7 GPa) and tensile strength by about 50% (from 300 to 450 MPa). The non‐edible protein and starch were extracted from defatted karanja ( Pongamia pinnata ) and mango ( Mangifera indica ) seed cake wastes, respectively, to prepare the green resins. Composite specimens were fabricated using as‐received and modified fibers and agro‐waste derived resins using a hand lay‐up process followed by hot‐pressing. The tensile properties of the composites made with modified fibers showed significant improvement as compared to the composites made with as‐received fibers as well as other edible starch or protein‐based sisal composites. POLYM. COMPOS., 40:99–108, 2019. © 2017 Society of Plastics Engineers